2022
DOI: 10.1111/os.13602
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Hyaluronic Acid Intra‐articular Injection after Arthroscopic Knee Surgery: A Systematic Review and Meta‐analysis

Abstract: Objective Hyaluronic acid (HA) intra‐articular injection after arthroscopic knee surgery has been widely applied but its efficacy and safety remain controversial. The aim of this systematic review is to analyze the efficacy and safety of HA intra‐articular injection after arthroscopic knee surgery, and to compare the efficacy of HA with different molecular weights. Methods We conducted a systematic literature search in PubMed, Embase, Google scholar and the Cochrane library from inception to 16 September 2022 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…It most frequently afflicts the knee joint 2 . Conservative treatments and arthroscopic surgery have been used as graded treatment methods with some success for these types of diseases 3 , 4 . However, total knee arthroplasty (TKA) is regarded as a tried-and-true treatment option for patients with end-stage knee joint disease 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It most frequently afflicts the knee joint 2 . Conservative treatments and arthroscopic surgery have been used as graded treatment methods with some success for these types of diseases 3 , 4 . However, total knee arthroplasty (TKA) is regarded as a tried-and-true treatment option for patients with end-stage knee joint disease 1 .…”
Section: Introductionmentioning
confidence: 99%
“…22 HA injections in the knee have been well studied, demonstrating inconsistent results. 23 The use of HA in the hip has been growing in popularity and has similarly demonstrated inconsistent results. A systematic review of randomized control trials by Wu et al 24 demonstrated that HA provided an improvement in pain and function for patients with osteoarthritis.…”
Section: Hyaluronic Acidmentioning
confidence: 99%
“…It is a natural therapeutic of interest, as arthritic joints display up to a 50% reduction in HA concentration 22 . HA injections in the knee have been well studied, demonstrating inconsistent results 23 . The use of HA in the hip has been growing in popularity and has similarly demonstrated inconsistent results.…”
Section: Nonoperative Managementmentioning
confidence: 99%
“…The authors reported significant improvements in the Western Ontario and McMaster University index function subscores 5 . However, recently, Mao et al (2023) systematically analyzed 15 studies involving 951 knees injected with HA after arthroscopic knee surgery. Although the meta-analysis showed that HA injection was safe, this therapy did not support pain relief or functional recovery 6 .…”
Section: Current Approaches For Treating Knee Osteoarthritis Hyaluron...mentioning
confidence: 99%
“…However, recently, Mao et al (2023) systematically analyzed 15 studies involving 951 knees injected with HA after arthroscopic knee surgery. Although the meta-analysis showed that HA injection was safe, this therapy did not support pain relief or functional recovery 6 . In 2020, Zheng et al performed a meta-analysis of 10 randomized controlled trials involving 998 patients to compare the effects of HA injection alone with those of combination therapy comprising acupuncture and HA injection.…”
Section: Current Approaches For Treating Knee Osteoarthritis Hyaluron...mentioning
confidence: 99%